Different Therapeutic Effects of CO2 and Diode Laser Irradiation on Tooth Movement-Related Pain - Tsuchiya, Takako; Hasegawa, Naoya; Yugawa, Misato; Sasaki, Au; Suda, Naoto; Adachi, Kazunori (Frontiers in Neurology, 2020)
Although orthodontic treatment is a common therapy to solve functional and aesthetic dental problems, pain induced by orthodontic force is observed at high incidence. To improve the comfort of the therapeutic environment, some analgesic approaches have been examined, including low-level laser therapy (LLLT). In dentistry, LLLT is mainly applied by two different lasers, CO2 and diode lasers, which are thought to have different biological actions associated with wavelength (CO2: 10,600 nm; diode: 808 nm). In addition to the effects on other orofacial pain (e.g., temporomandibular disorders and periodontitis), the analgesic effect of LLLT on orthodontic treatment-related pain is widely reported but not consistent. The aims of this study were 1) to determine whether irradiation by CO2 or diode lasers attenuates orthodontic pain using the jaw-opening reflex model, 2) to evaluate the optimal irradiation protocol for both lasers to obtain maximal analgesic effect on orthodontic pain and 3) to evaluate the effect of laser irradiation on tooth movement. In this animal model, orthodontic treatment-induced pain was observed most severely at one day after orthodontic force application, indicated by a significant reduction in the threshold for inducing the jaw-opening reflex on the orthodontically treated side compared with that of the contralateral side, and CO2 laser irradiation (30 or 600 s) to the orthodontic tooth region significantly increased the threshold for inducing the jaw-opening reflex. However, diode laser irradiation (30 and 600 s) did not alter the jaw-opening reflex threshold. On the other hand, neither CO2 nor diode laser irradiation altered jaw-opening reflex excitability in animals without orthodontic force application. In addition, when CO2 or diode laser irradiation (30 s) was applied immediately after orthodontic force application, a significant reduction in the jaw-opening reflex threshold on the next day was not observed. Laser irradiation did not alter tooth movement in the present study, however, an optimized irradiation protocol for aiding tooth movement was suggested. In conclusion, both CO2 and diode lasers are able to prevent orthodontic force-related pain. Furthermore, CO2 but not diode laser irradiation provides an analgesic effect after pain induction.